Explainable artificial intelligence model to predict acute critical illness from electronic health records - Simon Meyer Lauritsen; Mads Kristensen; Mathias Vassard Olsen; Morten Skaarup Larsen; Katrine Meyer Lauritsen; Marianne Johansson Jørgensen; Jeppe Lange; Bo Thiesson (Nature Communications, 2020)
Acute critical illness is often preceded by deterioration of routinely measured clinical parameters, e.g., blood pressure and heart rate. Here, the authors develop an explainable artificial intelligence early warning score system for its early detection.